Pengarahan Tentang Membangun Branding Merk Melalui Digital Marketing Menggunakan Media Sosial “Batik Semoi Nusantara” - Marsius Ferdnian; Muhammad Abdul Ghani; Athifa Zahra; Aprilia Kurnia Putri; Ika Septiani Taufan; Maharani Friska Marsanda; Emeraldy Nur Adam; Agchel Randa Bandaso; Bagus Ferry Prasetyo; Husniyah Husniyah; Fadhila Nayla Nugroho Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
The briefing on building Branding through Digital Marketing is the first step to creating modern MSMEs. This work program is used in the Real Work Lecture (KKN) program by students from the Faculty of Economics and Business, Balikpapan University in Argo Mulyo Village. This briefing aims to introduce products to potential consumers and increase product sales with a wider scope through Digital Marketing promotions. Batik Semoi Nusantara in Argo Mulyo Village is a Village-Owned Enterprise which produces handicrafts in the form of batik. The batik craftsmen are members of the Family Welfare Empowerment (PKK) in Argo Mulyo Village. The method implemented is guidance on how to promote Batik Semoi Nusantara products through digital marketing using social media such as Instagram as well as contributing to the creation of catalogues, business cards and feed templates for Instagram. The results of this briefing show increased awareness and understanding of Batik Semoi Nusantara in managing and using Digital Marketing through social media as a means of introducing and promoting batik products.